2011
DOI: 10.1111/j.1365-2958.2011.07662.x
|View full text |Cite
|
Sign up to set email alerts
|

TP0326, a Treponema pallidum β‐barrel assembly machinery A (BamA) orthologue and rare outer membrane protein

Abstract: SUMMARY Definitive identification of Treponema pallidum (Tp) rare outer membrane proteins (OMPs) has long eluded researchers. TP0326, the sole protein in Tp with sequence homology to a Gram-negative OMP, belongs to the BamA family of proteins essential for OM biogenesis. Structural modeling predicted that five polypeptide transport-associated (POTRA) domains comprise the N-terminus of TP0326, while the C-terminus forms an 18-stranded amphipathic β-barrel. Circular dichroism, heat-modifiability by SDS-PAGE, Tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
102
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 67 publications
(111 citation statements)
references
References 95 publications
(231 reference statements)
9
102
0
Order By: Relevance
“…This method is advantageous because it not only preserves the integrity of the spirochete's fragile OM during immunolabeling but also allows for its controlled removal by detergent solubilization in order to expose periplasmic antigens. Because T. pallidum expresses BamA at a very low copy number (ϳ100 molecules per cell) (34), at the outset, we confirmed that our rat ␤-barrel and POTRA antisera could recognize their target antigens at nanogram levels with recombinant proteins as well as in T. pallidum lysates (see Fig. S2 in the supplemental material).…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations
“…This method is advantageous because it not only preserves the integrity of the spirochete's fragile OM during immunolabeling but also allows for its controlled removal by detergent solubilization in order to expose periplasmic antigens. Because T. pallidum expresses BamA at a very low copy number (ϳ100 molecules per cell) (34), at the outset, we confirmed that our rat ␤-barrel and POTRA antisera could recognize their target antigens at nanogram levels with recombinant proteins as well as in T. pallidum lysates (see Fig. S2 in the supplemental material).…”
Section: Resultssupporting
confidence: 52%
“…Among our highest ranked candidates was TP_0326, discovered in 2000 as TP_92 by Cameron et al (19) using a differential screening strategy to identify opsonic targets in T. pallidum. Recently, we confirmed the status of TP_0326 as a bona fide rare OMP (34) and, using recombinant constructs, established that it possesses the bipartite topology characteristic of members of the Omp85 superfamily (7). In the present study, we demonstrated by indirect immunofluorescence analysis (IFA) of T. pallidum that only the ␤-barrel of native TP_0326 contains surface-exposed epitopes.…”
supporting
confidence: 50%
See 2 more Smart Citations
“…The CD spectra of all MOMP preparations had minima near 215 nm, which is indicative of β‐sheet secondary protein structure49, 50 and consistent with MOMP being a β‐barrel protein. CD spectra of β‐barrel outer membrane proteins such as MBOMP from Entamoeba , OMP P66 from Borrelia burgdorferi and BamA from Treponema pallidum have been reported in the literature 51, 52, 53. The shape of the CD spectra of these β‐barrel proteins is diverse with minima varying between 210 nm and 220 nm.…”
Section: Discussionmentioning
confidence: 99%